IMPLEMENTASI MANAJEMEN RISIKO PERUSAHAAN STUDI KASUS START UP CIRO WASTE - Reza Fahlevi, Mohammad; Deny Arthawan Sugih Prabowo, I Putu; Shauma Salsabiilla, Risqi’a; Amanda Aulia Putri, Ghea; Alyaa Farraas, Ghina; Nurhadi Efendi, Muhammad (LPPM ITK, 2025)
Sustainability-oriented waste management startups such as Ciro waste require comprehensive risk analysis to ensure operational stability and support long-term business growth. Despite operating in a highly regulated and complex sector—facing challenges such as strict environmental policies, raw material price volatility, and operational hazards including workplace accidents and ecological impacts—Ciro waste has yet to establish a documented risk management framework. This study aims to identify, evaluate, and design risk mitigation strategies aligned with the startup's business model. The methodology involves qualitative analysis of core business processes and risk mapping based on the ISO 31000 framework. The findings indicate that implementing a structured risk management approach not only minimizes potential operational disruptions but also enhances business resilience and strengthens the company’s reputation as a responsible and sustainable enterprise. These insights serve as a foundation for recommending the integration of risk management practices into Ciro waste’s overall business strategy, thereby fostering innovation in a competitive and sustainability-driven waste management industry.